História da fundação do Sindicato único dos trabalhadores da educação do Ceará (1983-1991) - Cheung, Fonlana (2021)
The study approached the history of the Sindicato Único dos Trabalhadores em Educação do Ceará (SINDIUTE), founded on December 15th, 1991, with the intention of representing the workers of the state and municipal public school networks of 1st and 2nd grade education in Ceará. The genesis of this unique union was the organizational result pursued by different entities and associations during the process of Brazilian re-democratization, in the 1980s. The debate about the unity among the entities had as its political mark the guidelines issued by the National Confederation of Education Workers (CNTE). The merger involved APEFCE (1948) which represented physical education teachers, ASSEC (1962) the educational supervisors, ASOECE (1962) the educational advisors, ASSECE (1962), APEOC/Sindicato (1962), and SINTECE (1990) the employees of the Secretariat of Education and/or Culture of the state and municipalities. Based on a historical-educational perspective the research tried to describe and analyze the process that culminated in the creation of SINDIUTE, by means of qualitative and quantitative research, with the use of semi-structured interviews, collection of testimonials, survey of documents of the entities involved, photographs, newspaper articles, and academic production pertinent to the theme studied.